Optimal ballast scheme design for cargo ships using an improved genetic algorithm. (25th February 2010) - Chen, Jing; Lin, Yan; Huo, Jun Zhou; Zhang, Ming Xia; , Zhuo Shang Ji
Loading design is a key stage in ships' design process, and directly affects ships' stability, strength, and attitude at sea. The problem of loading design is a multi-objective combinatorial optimisation problem with multiple nonlinear constraints. In this paper, based on the complex technical requirements of ships' loading design, a mathematical model was constructed, taking the overall longitudinal strength and the intact stability performances as objectives, and the limits of ship's attitude, stability and strength, etc. as constraints. A strategy of tanks being fully-loaded-first was adopted and the corresponding improved genetic algorithm was presented where a novel heuristic dynamic adjusting rule was proposed to dynamically adjust the normalising coefficients of the non-commensurable objectives. Finally, a real case study on the loading design of a 50, 000 DWT double hull product tanker was conducted to illustrate the effectiveness of the proposed method.